Examining needs support and positive developmental experiences through youth's leisure participation in a residential summer camp. Issue 3 (2nd July 2016) - Bean, Corliss N.; Kendellen, Kelsey; Forneris, Tanya
ABSTRACT: Summer camp represents an important leisure activity for youth. The purpose of this study was to explore if differences existed based on demographic variables (gender, age, years of camp experience, ethnicity) related to basic psychological needs support and positive developmental experiences, and to examine whether needs support predicted positive developmental experiences in youth within this context. Little research has examined if differences exist on these constructs based on various demographic variables and few studies have examined if needs support predicts these developmental experiences in youth who attend camp. This study aimed to address such gaps in the literature. Ninety-five youth who attended a 10-day residential summer camp completed two measures at the end of their camp experience. Results indicated differences existed based these identified demographic variables related to youth's perceived needs support and developmental experiences, and that needs support predicted positive developmental experiences.